(untitled) (Agro Productividad, 2023)
Objective: This work aimed to evaluate the microbiological safety of bioinputs produced in Mexico. The main reason for this evaluation is that bioinputs are products made from the region’s manures, plant residues and raw materials. The transformation of these raw materials is carried out by microorganisms present. The process goes through three stages: initial, thermophilic and final. The thermophilic stage is critical because weeds and microorganisms with pathogenic potential disappear in processes under optimal conditions. Methodology: 1345 bioinputs samples were received from different states of Mexico. The samples were evaluated for the presence of total and fecal coliforms and Escherichia coli under the provisions of the Official Mexican STANDARDS, NOM-210-SSA1-2014 and NOM-114-SSA1-1994. Results: It was possible to identify 79% of the samples with Most Probable Number values <3 of total coliforms, fecal coliforms and Escherichia coli, the minimum permissible by the Official Mexican STANDARD NOM-210-SSA1-2014, also identified 99% of samples free of Salmonella. Conclusions: The results obtained allow us to conclude that the bioinputs produced in Mexico are free of pathogens for humans, which can also be represented as innocuous bioinputs.